PENGEMBANGAN NILAI AGAMA DAN MORAL DALAM KELUARGA PADA ANAK USIA 5-6 TAHUN DI TK KARTINI PONTIANAK KOTA - Rini Rini; Aunurrahman Aunurrahman; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the development of religious and moral values in the family for children aged 5-6 years in Kartini Kindergarten Pontianak City. The research method used by the researcher in this study is a descriptive method with a qualitative research form. The subjects in this study were the parents of 27 children from the Kartini Kindergarten in Pontianak City in class B1 and B2. The research location is on Jalan. Sentarum Lake No. 75 Pontianak. Data collection techniques used in this study are observation techniques, interview techniques and documentation. The results of the study show that in general, through the example and habituation of parents who are practiced every day in the family, they can develop religious and moral values for children aged 5-6 years, with aspects so that children know their religion, so that children want to do worship, children can behave (honest, helpful, polite, respectful, sportsmanship and so on), so that children can maintain personal and environmental hygiene, know religious holidays, respect (tolerance) other people's religions.Keywords: Development, Family, Moral Values, And Religious